Hybrid model: a promising type of public procurement in the healthcare sector of the European Union - Geropoulos, Nikolaos; Voultsos, Polychronis; Geropoulos, Miltiadis; Tsolaki, Fani; Tagarakis, Georgios (Frontiers in Public Health, 2024)
The management of health supplies in public hospitals has been a major concern of national and European institutions over time, often being a field of reforms and regulatory interventions. Health procurement systems constitute complex decision-making and supply chain management mechanisms of public hospitals, involving suppliers, health providers, administrators and political bodies. Due to this complexity, the first important decision to be taken when designing a procurement system, concerns the degree of centralization, namely to what extent the decision-making power on the healthcare procurement (what, how and when) will be transferred either to a central public authority established for this purpose, or to the competent local authorities. In this perspective, we attempt to analyse the types of public procurement in the healthcare sector of the European Union, in terms of degree of centralization. Employing a narrative approach that summarizes recent interdisciplinary literature, this perspective finds that the healthcare procurement systems of the EU Member States, based on the degree of centralization, are categorised into three types of organizational structures: Centralized, Decentralized and Hybrid procurement. Each structure offers advantages and disadvantages for health systems. According to this perspective, a combination of centralized and decentralized purchases of medical supplies represents a promising hybrid model of healthcare procurement organization by bringing the benefits of two methods together.